Cervical smear cytology on routine screening in a semi urban population in New Delhi: A review of 610 cases - Safia Rana (Archives of Medicine and Health Sciences, 2013)
Background: Cervical cancer is an important public health problem among adult women in many developing countries. Cervical cytology became the standard screening test for cervical cancer and premalignant cervical lesions with the introduction of the Papanicolau (Pap) smear. The most widely used system for describing PAP smear result is the Bethesda System 2001. Material and Methods: This study was aimed at evaluating the entire spectrum of types and frequencies of cervical cytological abnormalities i.e. infective, pre-cancerous and cancerous, in women who underwent routine cytological cervical screening at our hospital which caters largely to women of low socio-economic status. Results: A total of 610 cases of cervical pap smears were received in our cytology laboratory during this two year period, 348(57%) abnormal Pap smears, and 238(39%) cases which were normal. Out of the 348 cases, 306(50.2%) cases were reported to have inflammatory/reactive/reparative changes whereas epithelial cell abnormality was reported in 42 cases. Discussion: Cervical smear cytology also plays an important role in the diagnosis of cervical infections which are common in women of the reproductive age group. Conclusion: Hence, the need of the hour is an effective screening programme that is based on available resources and is readily available to the low socio-economic and disadvantaged sections of our society.